Desain Pembelajaran PAI Efektif dengan Pendekatan Humanistik dan Spiritualitas Islam - Putri, Fadillah Julya; Fajtriansyah, Apriani Putri; Qonita Az Zahra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to design and analyze a more effective Islamic Religious Education (IRE) learning model by integrating humanistic principles with Islamic spirituality. This integration is important because traditional IRE learning has largely focused on cognitive mastery, while affective and spiritual dimensions have not been developed optimally. Using a descriptive qualitative method with a literature study approach, this research reviews books, academic journals, and previous studies relevant to humanistic and spiritual-based learning. Content analysis is then employed to identify thematic patterns that explain how both approaches can strengthen one another within the IRE learning process. The findings reveal that integrating humanistic and spiritual elements results in deeper, more reflective, and transformative learning experiences. The humanistic approach allows students to develop self-awareness, value personal experiences, and fulfill emotional needs, whereas Islamic spirituality reinforces the values of tawhid, moral character, and divine consciousness. Teachers play a crucial role as facilitators who guide students through learning experiences that combine humanistic empathy and Islamic values. Authentic assessment methods such as reflection journals, moral portfolios, and behavioral observations are used to evaluate student development. Overall, this study concludes that an IRE learning design grounded in both humanistic and spiritual approaches can foster intellectually capable, emotionally mature, and spiritually grounded learners who are well-prepared to face the challenges of the digital era.